WORK-LIFE BALANCE DAN INTENSI TURNOVER PADA PEKERJA WANITA BALI DI DESA ADAT SADING, MANGUPURA, BADUNG - Stepani Kartika Bintang; Dewi Puri Astiti (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2017)
A survey was held by US company, Randstad in 2012 showed that women worker reached a work-life balance, refers to man worker who were focus to reached the career goal. Women worker who take multiple role in their life, mostly had imbalance condition as a result. This condition will be trigger of turnover in women worker, even in Balinesse women worker who called Krama Banjar Istri too in their hometown village. The turnover condition can bring susceptible condition for the company from the cost recruitment effectiveness, the other side the employee will get lose out with re-adaptation from the new job of them (Abasi & Hollman, 2008). This research want to explain correlation between work-life balance and turnover intensity to describe how much impact of work-life balance to turnover intensity which done by Balinesse women worker in Sading village. This research involved by 206 subjects filled two scales which are work-life balance scale and turnover intention scale, both of it used simple random sampling method. The analysis used simple regression and descriptive analysis method. The result showed that significant negative correlation between work-life balance with turnover intensity. Effective contribution of work-life balance variable to turnover intention is 6.4%, while 93.6% of influenced by other factors. The factors that interfere work-life balance, thus triggering create imbalance conditions makes the subject decided the problem solving. Furthermore, the recommendation for the women worker shoud be perform time management wisely and involve the other member of the family to do homework. Key word: work-life balance, turnover intention, Balinesse women worker, imbalance, Sading village.